2003
DOI: 10.1152/ajpgi.00513.2002
|View full text |Cite
|
Sign up to set email alerts
|

Increasing cell membrane potential and GABAergic activity inhibits malignant hepatocyte growth

Abstract: Increasing hepatocyte membrane potentials by augmenting GABAergic activity inhibits nonmalignant hepatocyte proliferative activity. The objectives of this study were to document 1) potential differences (PDs) of four malignant hepatocyte cell lines, 2) GABAA receptor mRNA expression in the same cell lines, and 3) effects of restoring malignant hepatocyte PDs to levels approximating those of resting, nonmalignant hepatocytes. Hepatocyte PDs were documented in nonmalignant and malignant (Chang, HepG2, HuH-7, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 40 publications
3
28
0
Order By: Relevance
“…Thus, our finding of a 24% decrease in HCC tissue PD is not only consistent with these reports but also reports describing depolarization in various rat and human malignant cell lines. 2,22 Although the mechanism whereby such depolarization might result in enhanced cell proliferation and tumor growth remains to be determined, electrogenic translocation of polyvalent cationic growth promoters such as polyamines from the relatively positive-charged environment of the cytoplasm to the negative-charged DNA of the nucleus has been implicated. 23 Perhaps the most striking finding of the present study was the consistent and significant decrease in GABA A -␤3 receptor expression in HCC compared with adjacent nontumor tissues.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, our finding of a 24% decrease in HCC tissue PD is not only consistent with these reports but also reports describing depolarization in various rat and human malignant cell lines. 2,22 Although the mechanism whereby such depolarization might result in enhanced cell proliferation and tumor growth remains to be determined, electrogenic translocation of polyvalent cationic growth promoters such as polyamines from the relatively positive-charged environment of the cytoplasm to the negative-charged DNA of the nucleus has been implicated. 23 Perhaps the most striking finding of the present study was the consistent and significant decrease in GABA A -␤3 receptor expression in HCC compared with adjacent nontumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports previous descriptions of down-regulated or absent expression of this receptor isoform in human malignant hepatocyte cell lines and regenerating livers following partial hepatectomy. 2,6 Although the correlation of decreased receptor expression with increased proliferative activity may represent an association rather than effect, previous in vitro studies have shown that restoration and/or activation of GABA A -␤3 receptors results in attenuation of proliferative activity in malignant hepatocytes. 2,24,25 Moreover, reports of chromosomal deletions in the region encoding the GABA A -␤3 receptor gene being associated with hepatic tumor development in humans also argues in favor of a causative role.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations